Interioryzacja misterium paschalnego Chrystusa w celebracji Eucharystii - Stanisław T. Zarzycki (Polonia Sacra)
Starting from the difficulties in the reception of the Council’s teaching on the liturgy and its implementation, this article points to the need to discover the paschal mystery of Christ in the Eucharist. Because of the biblical and patristic-liturgical renewal and the re-emphasis on “mystery” in the twentieth century, the article introduces the concept of mystery in pagan cults and in the Church of the first centuries. The second part of the article, based John Paul II’s teaching on the Eucharist, shows the spiritual attitude towards the paschal mystery of Christ in the celebration of the Eucharist and considers the components of this attitude. At the same time, he takes into account signs and symbols and their functions in the interiorization of this mystery.